Clinical Features and Radiographic Aspects of Squamous Cell Carcinoma in the Gnathic Bones - Moura, Ludimila Lemes; Simpione, Guilherme; Peralta-Mamani, Mariela; Santos, Paulo Sérgio da Silva; Rubira, Cassia Maria Fischer; Rubira-Bullen, Izabel Regina Fischer (ARCHIVES OF HEALTH INVESTIGATION, 2023)
This integrative review aimed to discuss the clinical features and imaging aspects of squamous cell carcinoma in the gnathic bones on panoramic radiographs and cone-beam computed tomography. The electronic search was conducted in PubMed, Embase, and Scopus using the keywords cone-beam computed tomography, panoramic radiography, dentomaxillofacial complex, and oral squamous cell carcinoma. Studies between 2012 and 2022, report imaging aspects of the oral squamous cell carcinoma in panoramic radiography and cone-beam computed tomography were selected. The initial search found 375 articles, leaving 171 after excluding duplicates. Eighteen studies met the inclusion criteria, bringing together a total of twenty cases. Swelling and pain are common clinical features. In most cases, the squamous cell carcinoma was in the mandible; the borders were poorly defined with invasive aspects; the internal structure was radiolucent/hypodense and some cases, had radiopaque flecks. The lesion causes structures destroyed like the adjacent bone, the alveolar process, border of the mandibular canal, ramus of the mandible. The image aspects raised in this review: as large areas of osteolysis interspersed with an irregular pattern of radiopaque/hyperdense flakes, with imprecise limits and invasive borders, causing significant destruction of adjacent structures, squamous cell carcinoma can be a diagnostic hypothesis. In these cases, we recommend urgency in completing the diagnosis. The panoramic radiography can provide information that leads to the suspicion of a malignant lesion, but cone-beam computed tomography provides the real dimension and repercussion of the lesion.